Toxicologic evaluation of potassium polyaspartate (A-5D K/SD): Genotoxicity and subchronic toxicity. (November 2017) - Galbusera, C.; Casalegno, C.; Marroncelli, S.; Triulzi, G.; Santos, J.; Corsini, E.; Restani, P.
Abstract: Potassium polyaspartate (A-5D K/SD) is proposed for use as a stabiliser in wine, with a maximum use level of 300 mg/L and typical levels in the range of 100–200 mg/L. Potassium polyaspartate (A-5D K/SD) tested negative in a bacterial reverse mutation assay performed in accordance with OECD TG 471 and in an in vitro mammalian cell micronucleus test performed in accordance with OECD TG 487. From a 90-day oral toxicity study in male and female Wistar rats performed in accordance with OECD TG 408, a no observed adverse effect level (NOAEL) was set at 1000 mg/kg bw per day, the highest dose tested. In its opinion adopted on 9 March 2016, the EFSA-ANS Panel (European Food Safety Authority - Panel on Food Additives and Nutrient Sources added to Food), considering these data, concluded that "there was no safety concern from the proposed use and use levels of potassium polyaspartate (A-5D K/SD)". Highlights: Potassium polyaspartate (A-5D K/SD) was not mutagenic and showed no genotoxic activity. The NOAEL of the 90-day study was set at 1000 mg/kg bw/d—the highest dose tested. Results support that there is no safety concern from the proposed use and use levels of A-5D K/SD as a stabiliser in wine.